Daya Cipta and Islamic Innovation: A New Lens on Human Rights in Malaysia Madani (Contrarius Series: Law & Social Justice, 2026)
This study examines Daya Cipta as a core pillar of Islamic innovation within the Malaysia Madani framework and its implications for reimagining human rights from an Islamic perspective. Grounded in the Qur’an, Sunnah and the intellectual tradition of ijtihad and maqasid syariah, Daya Cipta is conceptualised as a value-driven form of creativity that integrates ethical responsibility, spiritual consciousness and societal well-being. Using a qualitative approach based on textual analysis of policy documents, classical Islamic sources, and contemporary human rights literature, the findings reveal three key insights. First, Daya Cipta is not a novel policy construct but an extension of Islamic epistemology that positions creativity and innovation as moral obligations tied to human dignity and stewardship (khilafah). Second, the Malaysia Madani framework reframes human rights by embedding them within a relational model that balances individual entitlements with communal responsibility, ethical accountability and spiritual values. Third, comparative analysis of selected development and governance indicators suggests that innovation guided by Islamic values can support sustainable human development without detaching rights from morality. Overall, the study demonstrates that Islamic innovation through Daya Cipta offers a new analytical lens for human rights discourse, one that moves beyond secular universalism toward a more holistic, humane and contextually grounded model of governance. This research contributes to the growing scholarship on Islam and human rights by illustrating how creativity, when anchored in Islamic principles, can function as a transformative force for ethical governance and sustainable societal progress in Malaysia Madani.